What determines bank stock price synchronicity? Global evidence - Bill Francis; Iftekhar Hasan; Liang Song; Bernard Yeung (Bank of Finland, 2012)
This paper examines what institutional and bank-specific factors determine bank stock price synchronicity. Using data on 37 countries from 1996-2007, we find that bank stocks are more aligned with the whole market (1) during the financial crisis; (2) in countries that have more credit provided by banks; (3) in countries that do not have explicit depository insurance; and (4) in countries that have lower bank-level disclosure. The results hold for both emerging and developed economy subsamples. Furthermore, in emerging economies, bank stocks in countries with higher degree of state-owned bank are more synchronized with the whole market, similarly, in developed markets, lower banking freedom enhances bank stock price synchronicity. Finally, the effects of state ownership, protection of property rights, and bank size are all more pronounced when determining bank stock price synchronicity during the financial crisis period.
URN:NBN:fi:bof-20140807669
Keywords: G12; G14; G15; G21; G38; N20; 330; stock price synchronicity; financial crisis; bank ownership; deposit insurance; banking freedom; bank disclosure